Plasmid profiles of antibiotic-resistant opportunistic strains of the Enterobacteriaceae family in the microbiota of men with urogenital tract inflammatory pathology - T. Sklyar; N. Kurahina; T. Lykholat; O. Lykholat; M. Papiashvili (Regulatory Mechanisms in Biosystems, 2025)
Bacterial resistance to antimicrobial drugs is a serious public health problem. Plasmids represent one of the most diff i cult problems in combating the spread of antibiotic resistance. The article presents the results of a real-time PCR study of the microbiota of 257 men with inflammatory processes of the urogenital tract. The role of representatives of the opportunistic microbiota in the occurrence of infectious and inflammatory processes of the urogenital system in men was established. The composition of the microbiota was represented by bacteria of the Enterobacteriaceae family in 39.3% of cases, Enter o coccus spp. – 10.9%, Haemophilus spp. – 3.1% and Pseudomonas aeruginosa – in 0.4% of cases. Analysis of the antibiotic sensitivity spectra of the bacterial intestinal group allowed us to establish that among the isolated enterobacteria monoresi s tance to ampicillin (21 – 23%) and resistance to ampicillin and amoxicillin/clavulanate (11 – 14%) were the most common. The work also revealed multiple resistance of clinical strains of enterobacteria to antibiotics: 8% of strains were found to be resistant to cephalosporins of the 3rd and 4th generations and ampicillin, i.e. to β-lactams (phenotype ApCpmCtaCrdCtx); 5% of strains were resistant to 7 and 9 drugs. For Escherichia , Klebsiella and Proteus (resistance to Ap and Ap Am/Cl) only two spectra were characteristic. At the same time, seven spectra were common to Es c herichia coli and Klebsiella sp., five – to E. coli and Proteus sp., three – to Proteus sp. and Klebsiella sp. Plasmids of different sizes were isolated from clinical polyresistant strains of E. coli , Proteus mirabilis , Klebsiella oxytoca . However, some multiresistant strains didn’t contain plasmids. Direct relationship between antibiotic resistance and the plasmid profile of E. coli wasn’t found. In experimental clinical strains of enterobacteria the presence of such plasmid spectrum opens up prospects for studying the widespread distribution of multidrug-resistant strains.